De-Rigging Elections: Direct Democracy and the Future of Redistricting Reform - Michael S. Kang (Washington University Law Review, 2006)
I propose direct democracy as the best solution, a distinctly political solution, to the problems of contemporary gerrymandering. By requiring direct democratic approval by the general electorate for passage of any statewide redistricting plan, direct democracy invites the public into civic engagement about the fundamental issues of democratic governance that a democracy ought to embrace. In Part II, I briefly describe redistricting reform efforts to transfer greater responsibility for redistricting to apolitical institutions, namely courts and independent commissions. In Part III, I argue that these efforts to insulate redistricting from politics are badly misguided. I contend that redistricting, as a fundamental political matter, requires popular participation and a process of democratic debate and compromise to strike the basic value tradeoffs tied up in redistricting. I conclude that redistricting reform is needed but requires a middle path between skeptics of reform and the shape of current reform efforts. In Part IV, I propose new use of direct democracy as the viable third way for redistricting reform. I describe how a basic requirement of direct democratic approval for redistricting legislation would moderate partisan gerrymandering, induce the major parties to compete for public approval, and draw the public into a healthier political process.
Keywords: Direct democracy; Apportionment (Election law); Electoral reform